Advanced Care Planning in Parkinson's Disease: In-depth Interviews With Patients on Experiences and Needs - Kurpershoek, Elisabeth; Hillen, Marij A.; Medendorp, Niki M.; de Bie, Rob M. A.; de Visser, Marianne; Dijk, Joke M. (Frontiers in Neurology, 2021)
Introduction: Advance Care Planning (ACP) is an iterative process of discussing patients’ needs, wishes, and preferences regarding disease-specific and end-of-life issues. There is ample evidence that ACP improves quality of life and promotes autonomy of patients with cancer and motor neuron disease which have a high disease burden and shortened life expectancy. In Parkinson’s disease (PD) though, knowledge about the experiences and preferences of patients regarding ACP is scarce, despite the major disease burden associated with PD. Aim: To explore experiences, needs and preferences of PD patients regarding content and timing of ACP. Methods: In-depth interviews were conducted with a purposively selected sample of patients diagnosed with PD. Participants were asked about their prospects for a future living with PD and with whom they wanted to discuss this, using a semi-structured topic list. Qualitative analysis was performed in parallel with data collection using a data driven constant comparative approach. Transcribed interviews were coded and analyzed by two researchers using MAXQDA software. Results: Of all 20 patients (13 male gender; age 47-82; disease duration 1-27 years), most expressed a wish to talk about ACP with a healthcare provider enabling them to anticipate the uncertain future. The majority of patients preferred their healthcare provider to initiate the discussion on ACP, preferably at an early stage of the disease. Nearly all patients expressed the wish to receive more information regarding the long-term impact of PD, although the preferred timing varied between patients. They also perceived that their neurologist was primarily focused on medication and had little time to address their need of a more holistic approach towards living with PD. Conclusion: Our results suggest that PD patients are in need of discussing ACP with their health care provider (HCP), even in early stages of the disease. In addition, PD patients perceive a lack of information on their disease course, and miss guidance on available supportive care. We recommend HCPs to inquire the information requirements and preferences of patients regarding ACP regularly, starting soon after diagnosis.